Braveheart - Gibson, Mel.; Ladd, Alan, 1937-; Davey, Bruce; Wallace, Randall; Marceau, Sophie, 1966-; McGoohan, Patrick, 1928-; Icon Productions; Ladd Company; Paramount Pictures Corporation (Hollywood, CA : Paramount, 2000)
William Wallace is a bold Scotsman who used the steel of his blade and the fire of his intellect to rally his countrymen to liberation.
DVD.
In English and French language soundtracks ; closed-captioned in English for the hearing impaired.
Mel Gibson, Sophie Marceau, Patrick McGoohan, Catherine McCormack.
Director of photography, John Toll ; editor, Steven Rosenblum ; music, James Horner.
Widescreen format.
Based on the book by Randall Wallace.
Keywords: Wallace, William, -- Sir, -- d. 1305 -- Drama; Scotland -- History -- Wallace's Rising, 1297-1304 -- Drama; Insurgency -- Scotland -- Drama; Wallace, William, -- Sir, -- d. 1305 -- Drama; Scotland -- History -- Wallace's Rising, 1297-1304 -- Drama; Insurgency -- Scotland -- Drama; Historical films; Feature films; Video recordings for the hearing impaired